DIVERSIFICATION OF SOCIAL PERSONAL GUIDANCE AND COUNSELING SERVICES IN RAUDLATUL ATHFAL (RA) CENDERAWASIH - Utsman, Ahmad Farid; Ulfa, Ulfa (Universitas Al-Hikmah Indonesia, 2023)
Diversification plays a very important role and is related to a strategy to overcome certain problems, the relationship with counseling services explains that diversification is a strategy to expand the methods and approaches used by counsellors to help clients solve problems. Guidance and counseling services in early childhood education in practice have their own challenges. Conditions in the field illustrate that the guidance and counseling services of Raudhlatul Athfal (RA) Cendrawasih early childhood education have several problems, one of which is related to the approach to a student. Diversification in guidance and counseling services needs to be done because of the urgency of providing guidance and counseling services to optimise the potential of early childhood, so in this case it is necessary that RA (PAUD) teachers must be able to understand the content of guidance and counseling so that they are able to insert social personal guidance and counseling content into RA (PAUD) learning activities. The method used in this research is descriptive using a qualitative approach. Sampling based on purposive sampling by determining the criteria that are considered representative in the study. So the researcher determined the number of samples consisting of 10 teachers at Raudlatul Athfal (RA) and also 20 students. This study provides the results that the diversification of social personal counseling guidance services uses 4 aspects of services, namely: orientation services that focus on environmental recognition, information services that focus on creating good communication and activities at school and determining and directing life goals, classroom services that aim to help learn comfortably according to the character of the child, and group guidance with the application of learning